Treatment of Knee Osteochondral Lesions Using a Novel Clot of Autologous Plasma Rich in Growth Factors Mixed with Healthy Hyaline Cartilage Chips and Intra-Articular Injection of PRGF - Ramón Cugat; Eduard Alentorn-Geli; Gilbert Steinbacher; Pedro Álvarez-Díaz; Xavier Cuscó; Roberto Seijas; David Barastegui; Jordi Navarro; Patricia Laiz; Montserrat García-Balletbó (Case Reports in Orthopedics)
Knee cartilage or osteochondral lesions are common and challenging injuries. To date, most symptomatic lesions warrant surgical treatment. We present two cases of patients with knee osteochondral defects treated with a one-step surgical procedure consisting of an autologous-based matrix composed of healthy hyaline cartilage chips, mixed plasma poor-rich in platelets clot, and plasma rich in growth factors (PRGF). Both patients returned to playing soccer at the preinjury activity level and demonstrated excellent defect filling in both magnetic resonance imaging and second-look arthroscopy (in one of them). The use of a clot of autologous plasma poor in platelets with healthy hyaline cartilage chips and intra-articular injection of plasma rich in platelets is an effective, easy, and cheap option to treat knee cartilage injuries in young and athletic patients.